2015
DOI: 10.4067/s0717-97072015000400007
|View full text |Cite
|
Sign up to set email alerts
|

Investigated the Supramolecular Interaction of Tramadol Hydrochloride With P-Sulfonated Calix[4,6,8]arene

Abstract: In this paper, the interaction behavior of p-sulfonated calix[n]arene (SCnA) with tramadol hydrochloride was investigated by fluorescence spectra, 1 H NMR spectra, and theoretical calculations in aqueous solution. At the optimized conditions, the fluorescence intensity of tramadol hydrochloride showed positive correlation to the concentration of SCnA, which led to a validated, simple, and sensitive fluorescence quenching method for the determination of tramadol hydrochloride was established for the first time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The results suggest that the electronegativity, polarization, hydrophobicity, FIP, hydrogen bonding potential, as well as the size and shape of the molecules may play an important role in the binding ability between alkaloids and SCnA. In addition, it has been reported in the literature that electrostatic interactions and structure-matching effects may be the main stabilizing factors of the host–guest complexes, , which is consistent with our findings and further validates the reliability of our predictions. These properties can be used for subsequent screening of compounds with a strong binding ability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results suggest that the electronegativity, polarization, hydrophobicity, FIP, hydrogen bonding potential, as well as the size and shape of the molecules may play an important role in the binding ability between alkaloids and SCnA. In addition, it has been reported in the literature that electrostatic interactions and structure-matching effects may be the main stabilizing factors of the host–guest complexes, , which is consistent with our findings and further validates the reliability of our predictions. These properties can be used for subsequent screening of compounds with a strong binding ability.…”
Section: Discussionsupporting
confidence: 92%
“…The negatively charged sulfonate on the upper rim provides electrostatic interaction sites, resulting in a strong binding ability and high selectivity toward various organic cations. Zhao et al 49 investigated the interaction between tramadol hydrochloride and SC4A, SC6A, and SC8A. The results showed that the binding constants of SCnA were more sensitive to changes in pH as the size of the SCnA cavity increased in the pH range from 2 to 11, suggesting that electrostatic interactions and structure-matching effects were the main stabilizing factors for the host−guest complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the wide variety of calixarenes, the most studied compounds for these purposes are water-soluble calix [4,6,8]arene sulfonic acids [ 29 ]. They form strong nanostructural supramolecular complexes with the known active pharmaceutical ingredients (APIs): binuclear platinum complexes (ovarian cancer treatment) [ 30 ], 3-phenyl-1H [1]benzofuro [3,2-c]pyrazole (tyrosine kinase III inhibitor) [ 31 ], Carvediol (management of hypertension) [ 32 ], Doxorubicin (antibiotic, a broad-spectrum anti-cancer drug) [ 33 ], Paclitaxel (ovarian, breast, lung and colon cancer treatment) [ 34 ], Tramadol (analgesic) [ 35 ], Nedaplatin (antineoplastic)…”
Section: Introductionmentioning
confidence: 99%